2011
DOI: 10.1248/bpb.34.128
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidant Effects of Kiwi Fruit in Vitro and in Vivo

Abstract: We previously reported that kiwi fruit is rich in polyphenols and has immunostimulatory activity. Polyphenols are widely known for having anti-oxidant effects. We also revealed potential anti-oxidant effects of kiwi fruit in vivo by oral administration to mice. Here, we compared the anti-oxidant effects of kiwi fruit with those of other fruits in vitro. Then, we examined the inhibitory effects of kiwi fruit on oxidation in the human body. There are two varieties of kiwi fruit, green kiwi and gold kiwi. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 34 publications
(33 reference statements)
2
37
0
2
Order By: Relevance
“…[1][2][3] Most used kiwi fruits have several cultivars, which differ significantly. [4] To distinguish and compare the cultivars, it is necessary to apply rapid analytical methods.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Most used kiwi fruits have several cultivars, which differ significantly. [4] To distinguish and compare the cultivars, it is necessary to apply rapid analytical methods.…”
Section: Introductionmentioning
confidence: 99%
“…While many research gaps remain, kiwi fruit with their multiple health benefits have the potential to become part of our "daily prescription for health" (Burdon et al, 2004;Stonehouse et al, 2013). Comparison of the antioxidant effects in vitro demonstrated that kiwi fruit had stronger antioxidant effects than orange and grapefruit, which are rich in vitamin C; gold kiwi had the strongest antioxidant effects (Iwasawa, Morita, Yui, & Yamazaki, 2011). Different treatments for the prolonged shelf life of fruits were ethylene treatment with combination of cold storage or room temperature (Mworia et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the antioxidant effects in vitro demonstrated that kiwi fruit had stronger antioxidant effects than oranges and grapefruits, which are rich in vitamin C, and gold kiwi fruit had the strongest antioxidant effects [2].…”
Section: Introductionmentioning
confidence: 99%